CD34+ STEM CELL MOBILISATION IN MS TREATMENT AND RELAPSE. Issue 10 (9th September 2014) - Witherick, Jonathan; Virgo, Paul; Redondo, Juliana; Cottrell, David; Scolding, Neil; Rice, Claire
Abstract : Release of CD34+ haematopoietic stem cells (HSC) into the peripheral circulation has been demonstrated in patients receiving anti-CD49d monoclonal antibody for the treatment of multiple sclerosis (MS). It is not known whether these cells are mobilised during an acute MS relapse or by treatment with other disease-modifying drugs (DMDs). We analysed peripheral blood samples from patients with MS including those on disease modifying therapy and during acute relapses. Circulating numbers of CD34/133+ cells were determined using flow cytometry. A novel, multi-channel flow cytometric approach was developed to identify multipotent mesenchymal stromal cells (MSCs). The finding of mobilisation of CD34+ HSCs with anti-CD49d antibody infusion was replicated. Increases in circulating numbers of CD34+ HSCs were also observed in patients treated with glatiramer acetate and in MS patients experiencing an acute relapse, irrespective of ongoing treatment with DMDs. CD133+ subsets were also increased in all groups. Circulating MSCs were not detected in the peripheral blood of patients or controls. Our results suggest a role for HSC mobilisation during treatment for MS and in acute relapse. Further work will examine the role of these cells in the pathogenesis of MS and endogenous repair.